Chromatin, nuclear lamins, and maintenance of the differentiated identity. Issue 11 (October 2018) - Bitman-Lotan, Eliya; Orian, Amir
Abstract: How differentiated cells maintain their identity is a fundamental question in biology. Loss of identity is a hallmark of aged cells and tissues, and is associated with age-related diseases such as neurodegeneration, metabolic disorders and cancer. It is an active process that requires dedicated transcription factor networks. Recent findings suggest that another level of identity regulation involves maintenance of nuclear organization that is unique to the differentiated cell and is dependent on nuclear lamins. Here we review the current understanding of the mechanisms and regulators that maintain the differentiated identity by connecting chromatin state with large-scale organization of the nucleus. We forecast that mechanisms involved in supervising cell identity will be highly relevant to aging biology, cancer, and regenerative medicine. Highlights: Maintaining the differentiated state requires continues supervision. Large-scale nuclear organization is essential for maintaining identity. Tethering heterochromatin to nuclear periphery is essential for gene silencing. Nuclear lamins actively regulate gene-silencing and maintain cell identity. Mechanisms ensuring differentiated identity are a natural barrier to reprograming.